The High Accurate Automatic School Bell Controller Based On Arduino Uno DS1307 I2C Real-time Clock - Dinda, Rizka Anggia; Sadrina, Sadrina; Mursyidin, Mursyidin (Jurnal Teknik Mesin Mechanical Xplore, 2023)
Education plays a crucial role in developing human resources with the necessary character and competence to meet the demands of the future Industrial 4.0 revolution. To ensure the effectiveness of the teaching and learning process, schools require supporting facilities and infrastructure. One such component is the school bell, which helps teachers notify students of daily schedules. As technology advances, some schools have adopted an automatic school bell as an alternative to traditional bells. These automatic school bells use Arduino microcontroller technology to ring at scheduled times, automatically improving accuracy and convenience. By utilizing sound output via an Arduino-based system, every created information can be easily delivered and reached. This study follows the System Development Life Cycle (SDLC) method, a widely used system development methodology encompassing hardware and software systems. The research successfully demonstrates an automatic school bell system capable of automatically producing notification sounds, optimizing electricity consumption, and generating precise sound frequencies during teaching and learning activities. The output voltage and current results at various parts of the automatic school bell system range from 4.17 to 5.90 volts and 488 to 602 mA, respectively. At the same time, power consumption achieved about 2.07 to 3.38 Watts. An automatic school bell system simplifies ringing the school bell as it seamlessly integrates with the scheduled timetable (software). As a result, the automatic school bell now rings automatically according to the pre-defined schedule, enhancing efficiency and ensuring timely transitions between classes and breaks.